Transforming positive risk-taking practices: the possibilities of creativity and resilience in learning disability contexts - Seale, J; Nind, M; Simmons, B (2013)
In this article we examine discourses, conceptualisations and practices of positive risk-taking for or by children and adults with learning disabilities. We identify tensions and contradictions in positive risk-taking discourses that are unhelpful for clarifying for practitioners how positive risk-taking might be implemented. We suggest a conceptual framework that incorporates creativity and resilience and use this to offer examples from special and inclusive education (Intensive Interaction and Learning without Limits) that illustrate how positive risk-taking can be found in education practices. We conclude by arguing that conceptual frameworks such as the one proposed, when linked to supportive frameworks and guiding principles that emphasise professional judgement, offer one way to problematise and challenge current risk-averse practices in education, health and social care settings. © 2013 Copyright Nordic Network on Disability Research.